Calculation of Comparison of Efficiency of Main Driving Machine Sister Ship - Henny Pasandang Nari (Ridwan Institute, 2023)
The purpose of this study is to calculate the efficiency ratio of the main propulsion engine of the sister ship. Based on the research focus that has been described in the problem formulation, the type of research used is a type of quantitative research using comparative descriptive methods. This study took data on 2 (two) PELNI passenger ships docked at Makassar port, namely KM Bukit Siguntang and KM Lambelu. The process of data collection, data processing and analyzing research data lasted for 4 (four) months from June to September 2022. From the results of data processing contained in the results of research and discussion, it can be concluded that KM Lambelu engine efficiency of 44.145% where specific fuel consumption is 0.1848. KM Bukit Siguntang engine efficiency of 44.07% where specific fuel consumption is 0.1851.